The Johnson GEO CENTRE:: Earth’s Geological Showcase - Blackwood, R. (Geoscience Canada, 2009)
SUMMARY The Johnson GEO CENTRE is a geological museum in St. John’s. It was built by Mr. Paul Johnson, a retired St. John’s businessman and philanthropist, after he became captivated by geology. The uniquely constructed CENTRE has several exhibits that explain the fundamentals of geoscience, demonstrate Earth history through the geology of Newfoundland and Labrador, show the evolution and world-wide migration of human beings, and emphasize the importance of Earth resources and good stewardship to the future of Earth’s peoples. Students are welcomed by entertaining, curriculum-based, geo-education programs. These and other public-awareness-of-geo-science activities are the main focus for GEO’s dedicated staff and volunteers.